2013
DOI: 10.1007/s10495-013-0883-x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-secretase inhibition attenuates oxaliplatin-induced apoptosis through increased Mcl-1 and/or Bcl-xL in human colon cancer cells

Abstract: The Notch signaling pathway plays a significant role in differentiation, proliferation, apoptosis, and stem cell processes. It is essential for maintenance of the normal colon crypt and has been implicated in colorectal cancer oncogenesis. Downregulation of the Notch pathway through gamma-secretase inhibitors (GSIs) has been shown to induce apoptosis and enhance response to chemotherapy in a variety of malignancies. In this study, we analyzed the effect of MRK-003 (Merck), a potent inhibitor of gamma-secretase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…It is well known Notch pathway interacts with many different signaling cascades to regulate critical cellular processes (26). In different cancers, the inhibition of Notch-1 has been reported to induce G2/M cell cycle arrest (33), upregulate apoptosis via anti- BCL-XL,BCL-2 (34, 35), and impair phosphorylation of MEK (36) and AKT (37). Our results reflect that GSI treatment of prostate cancer involves many of these activities and thus suggest that the anti-tumor effects of Notch inhibition in prostate cancer involves multiple mechanisms that culminate in an overall inhibition of tumor growth through both inhibition of proliferation and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known Notch pathway interacts with many different signaling cascades to regulate critical cellular processes (26). In different cancers, the inhibition of Notch-1 has been reported to induce G2/M cell cycle arrest (33), upregulate apoptosis via anti- BCL-XL,BCL-2 (34, 35), and impair phosphorylation of MEK (36) and AKT (37). Our results reflect that GSI treatment of prostate cancer involves many of these activities and thus suggest that the anti-tumor effects of Notch inhibition in prostate cancer involves multiple mechanisms that culminate in an overall inhibition of tumor growth through both inhibition of proliferation and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-cascade is controlled by some molecules and is crucial in cell apoptosis. The ratio of Bax/Bcl-2 usually determined the cell apoptosis (Timme et al, 2013;Yang et al, 2013) and activated caspase-cascade or not. In our present study, mIDH1 and wIDH1 over expression didn't cause apoptosis changes under routine condition.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al (34) reported that oxaliplatininduced colorectal cancer cell apoptosis was enhanced by apoptosis stimulated protein of p53-2 (ASPP2) via inhibition of autophagy. Timme et al (35) showed that increased protein levels of Mcl-1 and/or Bcl-xL as well as reduction in Bax and Bak activation attenuated oxaliplatin-induced apoptosis in human colon cancer cells. Shan et al (36) indicated that downregulation of RIP1 promoted oxaliplatin-induced apoptosis in tongue squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%